2016
DOI: 10.4236/jectc.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Combined Radiation and Forced Convection Heat Transfer in 3D Laminar Flow over an Inclined Forward Facing Step

Abstract: In the current study, a numerical investigation of three-dimensional combined convection-radiation heat transfer over an inclined forward facing step (FFS) in a horizontal rectangular duct is presented. The fluid is treated as a gray, absorbing, emitting and scattering medium. To simulate the incline surface of FFS, the blocked-off method is employed in this study. The set of governing equations for gas flow are solved numerically using the CFD technique to obtain the temperature and velocity fields. Since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…To compare the results, the distribution of Nunormalc ${\text{Nu}}_{{\rm{c}}}$ over the upstream of the step is plotted in (Figure 3B). Both the obtained result and the results from Rayeni and Nassab 45 are closely matching. Hence, it is confirmed that the code can model RHT.…”
Section: Mathematical Modelingsupporting
confidence: 77%
See 3 more Smart Citations
“…To compare the results, the distribution of Nunormalc ${\text{Nu}}_{{\rm{c}}}$ over the upstream of the step is plotted in (Figure 3B). Both the obtained result and the results from Rayeni and Nassab 45 are closely matching. Hence, it is confirmed that the code can model RHT.…”
Section: Mathematical Modelingsupporting
confidence: 77%
“…The RHT part of the analysis was validated from the research paper results of Rayeni and Nassab 45 by considering a laminar flow over a 3D FFS. Geometry with actual boundary conditions specified by Rayeni and Nassab 45 are given in Figure 3A.…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 2 more Smart Citations